2015
DOI: 10.1615/jlongtermeffmedimplants.2015012034
|View full text |Cite
|
Sign up to set email alerts
|

High Insertion Torque and Peri-Implant Bone Loss: Is There a Relationship?

Abstract: Because primary stability has a critical role in implant osseointegration, greater insertion torque is more desirable. However, excessive pressure on the peri-implant bone may lead to bone resorption. This study evaluates the effect of insertion torque on crestal bone level. Periapical radiographs of 136 bone-level implants were assessed in this retrospective cohort study. Sixty-four implants were inserted with high insertion torques (45-70 N/cm) and 72 implants were placed with a torque in the range of 20 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…In the study by Bidgoli et al . , insertion torque values of up to 70 Ncm did not significantly increase CBL around implants. Moreover, occlusal forces were minimised by narrowing the bucco‐lingual width of the occlusal table and by maintaining minimum centric contacts and complete disocclusion in eccentric movements.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In the study by Bidgoli et al . , insertion torque values of up to 70 Ncm did not significantly increase CBL around implants. Moreover, occlusal forces were minimised by narrowing the bucco‐lingual width of the occlusal table and by maintaining minimum centric contacts and complete disocclusion in eccentric movements.…”
Section: Discussionmentioning
confidence: 64%
“…It is therefore probable that in the present study, use of PS implants and implant insertion torques of <50 Ncm may have contributed towards the stability of peri‐implant crestal bone. However, contradictory results have also been reported . In the study by Bidgoli et al .…”
Section: Discussionmentioning
confidence: 94%
“…In this sense, Aldahlawi and Collaborates published that implants inserted with high insertion torque (>55 Ncm) showed more peri-implant bone loss than implants inserted with a less assertive insertion torque (<55 Ncm) [29]. Whereas, Bidgoli and collaborates related that the high insertion torques (up to 70 Ncm) did not generate a significant increase in periimplant bone resorption [31]. However, in our present study, the analysis of the influence regarding the value of insertion torque refers to its effects on cellular events during bone tissue healing around the implant surface (osseointegration phase) and, most of the articles above, relate the effects of torque degree on already integrated implants.…”
Section: Discussionmentioning
confidence: 99%
“…From a histological point of view, Trisi and colleagues reported higher bone apposition, primary stability, and removal torque values for a high insertion torque group compared to a lower torque group. A study by Bidgoli and colleagues assessed 64 implants placed at an insertion value of 45‐70 Ncm and 72 placed at a range of between 20 and 30 Ncm and found that high insertion values did not significantly increase bone resorption around dental implants.…”
Section: Discussionmentioning
confidence: 99%